The eye of the storm. - Robins, Kevin; Levidow, Les (Screen)
The article focuses on technologies used by the U.S. military in Operation Desert Storm. In this war, aircraft like the U.S. F-15E and the British Tornado were equipped with imaging systems that illuminate objects with infrared beams, allowing low attitude flying and location of targets during the night. The ultimate achievement introduced during the war is the Tomahawk cruise missile, which navigates through a radar altimeter which compares the topography of its flight path against detailed terrain maps stored in its memory.